Evaluasi Pengendalian Internal atas Aset Tetap pada PT WAN: Case Study of PT WAN, Logistics Company - Rika Lestari; Ancella Anitawati Hermawan (Politeknik Ganesha Medan, 2023)
This research aims to evaluate the implementation of the concept of internal control within the COSO framework for the procurement and management of fixed assets in an effort to increase the reliability of financial reports. PT WAN is a logistics service provider company by providing land transportation services. Dump trucks and heavy equipment are important components in business activities. Several incidents of errors in fixed assets such as discrepancies in recording and asset ownership status, also inadequate documentation. In addition, other fixed assets also have problems such as unrecorded and depreciated assets and ignorance of the acquisition value of assets. This made PT WAN have to initiate the right steps to suppress the problem. This study uses a case study method with a qualitative approach. The processed data is obtained from interviews, conducts observations, analysis internal documents and then evaluated based on COSO 2013 principles. The results showed that there are still deficiencies in internal control over the procurement and management of the company's fixed assets. These weaknesses are the unorganized flow of procurement, recording and sale of assets, not recording of all fixed assets, and lack of knowledge about the process of procuring and recording fixed assets. PT WAN must establish formal documents related to SOPs of fixed assets, labeling the company's equipment and tools, carrying out stock taking of fixed assets every month, re-managing data on all of the company's fixed assets, adding accounting personnel and providing training.